Analysis of Fault Characteristics of AC Line Interconnected with MMC. Issue 2 (March 2021) - Li, Dongsheng; Yang, Bingyuan; Xu, Shuo
Abstract: Affected by the control strategy of suppressing the negative sequence current and limiting the amplitude of the positive sequence current after the MMC fault, the fault characteristics of the converter side of the AC line interconnected with the MMC show that the negative sequence current is very small and the positive sequence current amplitude is different from the rated value Compared with the fault characteristics of the traditional power supply, there are obvious differences between the minor characteristics and the fault characteristics of the traditional power supply. And it has been simulated and verified on the RTDS simulation platform.